ASC annual report 1996/1997 (Annual report Australian Sports Commission, 1997)
The Australian Sports Commission (ASC) was established by the Australian Sports Commission Act 1989 and is the Commonwealth agency responsible for providing advice on, and delivering the Government's sport policy and programs. The ASC is a statutory authority with a Board of Commissioners appointed by the Government.